Labour laws in preindustrial Europe the coercion and regulation of wage labour, C. 1350-1850 - Whittle, Jane ca. 20./21. Jh; Lambrecht, Thijs (The Boydell Press, 2023)
Explores the variety of legal and regulatory regimes that existed in Western Europe to control labour and how workers experienced those controls.
Keywords: Geschichte 1350-1850; Arbeitsrecht; Lohnarbeit; Europa; Labor laws and legislation-Europe-History; Europe-Social conditions-To 1492; Electronic books; Aufsatzsammlung